Radiosensitivity in patients affected by ARPC1B deficiency: a new disease trait? - Chiriaco, Maria; Ursu, Giorgiana Madalina; Amodio, Donato; Cotugno, Nicola; Volpi, Stefano; Berardinelli, Francesco; Pizzi, Simone; Cifaldi, Cristina; Zoccolillo, Matteo; Prigione, Ignazia; Di Cesare, Silvia; Giancotta, Carmela; et al. (Frontiers in Immunology, 2022)
Actin Related Protein 2/3 Complex Subunit 1B (ARPC1B) deficiency is a recently described Inborn Error of Immunity (IEI) presenting with combined immunodeficiency and characterized by recurrent infections and thrombocytopenia. Manifestations of immune dysregulation including colitis, vasculitis and severe dermatitis, associated to eosinophilia, Hyper-IgA and Hyper-IgE are also described in ARPC1B-deficient patients. To date the hematopoietic stem cell transplantation seems to be the only curative option for patients. ARPC1B is part of the Actin-related protein 2/3 complex (Arp2/3) and cooperates with the Wiskott-Aldrich syndrome protein (WASp) in the regulation of the actin cytoskeleton remodeling and in driving double-strand breaks clustering for homology-directed repair. In this study we aimed to investigate radiosensitivity (RS) in ARPC1B-deficient patients to assess whether it can be considered an additional disease trait. At first, we performed trio-based next-generation-sequencing studies to obtain the ARPC1B molecular diagnosis in our index case characterized by increased RS, then we confirmed, using three different methods, an increment of radiosensitivity in all enrolled ARPC1B-deficient patients. Particularly, higher levels of chromatid-type aberrations and γH2AX foci, with an increased number of cells arrested in G2/M-phase of the cell cycle, were found in patients’ cells after ionizing radiation exposition and radiomimetic bleomycin treatment. Overall, our data suggest increased radiosensitivity as an additional trait in ARPC1B deficiency and support the necessity to investigate this feature in ARPC1B patients as well as in other IEI with cytoskeleton defects to address specific clinical follow up and optimize therapeutic interventions.